APLIKASI MODEL REKAYASA LAHAN TERPADU GUNA MENINGKATKAN PENINGKATAN PRODUKSI HORTIKULTURA SECARA BERKELANJUTAN DI LAHAN PASIR PANTAI - Kastono, Dody (Jurnal Ilmu-Ilmu Pertanian, 2007)
Coastal sandy land as a one of marginal land which potential become to be a sustainable productive land. Annual crops such as horticulture proper to developed as an agribusiness crops in coastal sandy land. Integrated land manipulation model consisted of applications i.e.: clay soil, organic fertilizer (manure), straw mulch, and plastic under bed as an impermeable layer with permanent or not permanent wind breaker, could improved growth and increased of yield productivity of horticulture crops reached 2.0-3.5 fold compared with agricultural model conventional farmers. Increasing yield was obtained by improving of land conditions and microclimate of crop environment which promoted growth and yield of horticulture.